2011
DOI: 10.1007/s10570-011-9500-8
|View full text |Cite
|
Sign up to set email alerts
|

Never-dried bacterial cellulose/fibrin composites: preparation, morphology and mechanical properties

Abstract: BC/fibrin composites having fibrin/BC weight percent ratios ranging from 2/98 to 64/36 were produced by immersing never-dried-BC into varying compositions of fibrin/ionic liquid/DMSO solutions and for increasing time periods. The composite compositions were predicted from an FTIR/Beer's law calibration method based on calibration samples which exhibited an RMSEP of 2.5 weight percent. Observations of the composite surface with atomic force microscopy and of the internal pore structure with scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
19
1
1
Order By: Relevance
“…strength, elasticity and durability (Kambic et al 1984). However, our earlier work on BC/fibrin composites (Brown et al 2011) showed only moderate improvements of mechanical properties as compared to native BC. In particular, the elasticity of the BC/fibrin composite as measured by the strain at break in static tensile test or the strain in low amplitude tensile cyclic creep testing was only moderately improved.…”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…strength, elasticity and durability (Kambic et al 1984). However, our earlier work on BC/fibrin composites (Brown et al 2011) showed only moderate improvements of mechanical properties as compared to native BC. In particular, the elasticity of the BC/fibrin composite as measured by the strain at break in static tensile test or the strain in low amplitude tensile cyclic creep testing was only moderately improved.…”
Section: Introductioncontrasting
confidence: 56%
“…In the present fabrication method, the fibrin content was apparently limited by the surface area of BC fibers available for interactions. Indeed, most of the fibrin that initially infiltrated the BC fiber networks, as observed in SEM images in the previous work (Brown et al 2011), disassociated from BC during glutaraldehyde-treatment. For example, an initial BC/fibrin composite with 61wt% fibrin was reduced to a 33wt% fibrin content after glutaraldehyde-treatment.…”
Section: Tensile Propertiesmentioning
confidence: 51%
See 1 more Smart Citation
“…Since BC is exposed to complex loading conditions of human-body environment, it is extremely important to characterize its viscoelastic properties in an explicit analytical form. Brown et al (2011Brown et al ( , 2012 quantified elastic and viscoelastic properties of a BC fibre-reinforced bio-composite with tensile and cyclic creep tests, demonstrating its suitability as a potential implant for artificial blood vessels. Nimeskern et al (2013) evaluated viscoelastic properties of BCs with various cellulose contents by means of stress-relaxation indentation; then, comparing the obtained data with those for ear cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…and a use as a scaffold material for both BC-based bio-composites (e.g. BC/fibrin composite for artificial blood vessel [10], BC/polyvinyl alcohol composite for artificial heart-valve leaflets [11], etc.) and in-vitro tissue regeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%